2011
DOI: 10.1371/journal.pone.0020793
|View full text |Cite
|
Sign up to set email alerts
|

The Oncoprotein EVI1 and the DNA Methyltransferase Dnmt3 Co-Operate in Binding and De Novo Methylation of Target DNA

Abstract: EVI1 has pleiotropic functions during murine embryogenesis and its targeted disruption leads to prenatal death by severely affecting the development of virtually all embryonic organs. However, its functions in adult tissues are still unclear. When inappropriately expressed, EVI1 becomes one of the most aggressive oncogenes associated with human hematopoietic and solid cancers. The mechanisms by which EVI1 transforms normal cells are unknown, but we showed recently that EVI1 indirectly upregulates self-renewal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 49 publications
1
32
0
Order By: Relevance
“…Development 139 (13) G9a (Gyory et al, 2004), Lsd1 ), Hdac2 (Yu et al, 2000), Prmt5 (Ancelin et al, 2006) Groucho family (Tle1 and Tle2) (Ren et al, 1999) and Irf4 (Gupta et al, 2001) Prdm2 H3K9 methlytransferase (Kim et al, 2003) p300 (Carling et al, 2004) Prdm2 homodimer (Huang et al, 1998), Rb1 (Buyse et al, 1995) and ER (Medici et al, 1999) Prdm3 p300 (Chakraborty et al, 2001), P/CAF, HDACs (Alliston et al, 2005), SuV39H1 (Cattaneo and Nucifora, 2008), Dnmt3a/b (Senyuk et al, 2011), Mbd3 (Spensberger et al, 2008), Uxt (McGilvray et al, 2007) and PRC (Yoshimi et al, 2011) CtBP (Izutsu et al, 2001;Palmer et al, 2001), Gata1 (Laricchia-Robbio et al, 2006), Jnk (Kurokawa et al, 2000;Spensberger et al, 2008), Runx1 (Senyuk et al, 2007), Smad1/2 (Alliston et al, 2005), Smad3 (Kurokawa et al, 1998) HDACs and p300 (Takahata et al, 2009) Ppar /Ppar , SKI (Takahata et al, 2009), Smad3 (Warner et al, 2007), CtBP , C/EBP ) and Ppargc1 /Ppargc1 (Seale et al, 2007) Bhlhb5, basic helix-loop-helix domain-containing class B5; C/EBP , (CCAAT/enhancer-binding protein ); CtBP, C-terminal binding protein; Dnmt, DNA methyltransferase; ER, oestrogen receptor; Gfi1, growth factor independent 1; HDAC, histone deacetylases; Irf4, interferon regulatory factor 4; Jnk, c-Jun N-terminal kinase; Lsd1, lysinespecific demethylase 1; Mbd3, methyl-CpG binding domain protein 3; Pu.1, SFFV proviral integration 1; P/CAF, p300/CBP-associated factor; Ppar, peroxisomeproliferator-activated receptor; Ppargc1, Ppar co-activator 1 ; Prc, Polycomb repressive complex; Prmt5, protein methyltransferase 5; Rb1, retinoblastoma 1; Runx1, runt-related transcription factor; Smad, MAD homologue; Tle, transducin-like enhancer of split; Uxt, ubiquitously transcribed tetratricopeptide r...…”
Section: Reviewmentioning
confidence: 99%
“…Development 139 (13) G9a (Gyory et al, 2004), Lsd1 ), Hdac2 (Yu et al, 2000), Prmt5 (Ancelin et al, 2006) Groucho family (Tle1 and Tle2) (Ren et al, 1999) and Irf4 (Gupta et al, 2001) Prdm2 H3K9 methlytransferase (Kim et al, 2003) p300 (Carling et al, 2004) Prdm2 homodimer (Huang et al, 1998), Rb1 (Buyse et al, 1995) and ER (Medici et al, 1999) Prdm3 p300 (Chakraborty et al, 2001), P/CAF, HDACs (Alliston et al, 2005), SuV39H1 (Cattaneo and Nucifora, 2008), Dnmt3a/b (Senyuk et al, 2011), Mbd3 (Spensberger et al, 2008), Uxt (McGilvray et al, 2007) and PRC (Yoshimi et al, 2011) CtBP (Izutsu et al, 2001;Palmer et al, 2001), Gata1 (Laricchia-Robbio et al, 2006), Jnk (Kurokawa et al, 2000;Spensberger et al, 2008), Runx1 (Senyuk et al, 2007), Smad1/2 (Alliston et al, 2005), Smad3 (Kurokawa et al, 1998) HDACs and p300 (Takahata et al, 2009) Ppar /Ppar , SKI (Takahata et al, 2009), Smad3 (Warner et al, 2007), CtBP , C/EBP ) and Ppargc1 /Ppargc1 (Seale et al, 2007) Bhlhb5, basic helix-loop-helix domain-containing class B5; C/EBP , (CCAAT/enhancer-binding protein ); CtBP, C-terminal binding protein; Dnmt, DNA methyltransferase; ER, oestrogen receptor; Gfi1, growth factor independent 1; HDAC, histone deacetylases; Irf4, interferon regulatory factor 4; Jnk, c-Jun N-terminal kinase; Lsd1, lysinespecific demethylase 1; Mbd3, methyl-CpG binding domain protein 3; Pu.1, SFFV proviral integration 1; P/CAF, p300/CBP-associated factor; Ppar, peroxisomeproliferator-activated receptor; Ppargc1, Ppar co-activator 1 ; Prc, Polycomb repressive complex; Prmt5, protein methyltransferase 5; Rb1, retinoblastoma 1; Runx1, runt-related transcription factor; Smad, MAD homologue; Tle, transducin-like enhancer of split; Uxt, ubiquitously transcribed tetratricopeptide r...…”
Section: Reviewmentioning
confidence: 99%
“…Because we recently found that EVI1 stimulates de novo DNA methylation in vivo (36,37), we evaluated the methylation status of the regulatory region of miR-9-3 in BM cells infected with the vector or EVI1. Direct sequencing of bisulfite-converted genomic DNA 10 d after infection clearly showed that EVI1 induces an increase of de novo DNA methylation in this miR-9-3 region.…”
Section: Evi1 Represses Mir-9 Expression By Hypermethylation Of the Pmentioning
confidence: 99%
“…5,6 EVI1 recruits a variety of transcriptional and epigenetic regulators, such as CTBP (C-terminalbinding protein), CBP (CREB-binding protein), P/CAF (P300/CBPassociated factor), HDAC (histone deacetylase), DNMT (DNAmethyltransferase), MBD3, or histone methyltransferases, suggesting a role in the control of gene expression. [7][8][9][10][11][12][13] Human EVI1-mediated disease can partly be recapitulated using in vitro and in vivo models. Aberrant expression of EVI1 in mouse BM precursors in vivo causes a disease which resembles myelodysplastic syndrome (MDS).…”
Section: Introductionmentioning
confidence: 99%